Do moms demand action on guns? Parenthood and gun policy attitudes. Issue 3 (3rd July 2022) - Greene, Steven; Deckman, Melissa; Elder, Laurel; Lizotte, Mary-Kate
ABSTRACT: The idea that motherhood primes women to support stronger gun control policy permeates our contemporary politics. Motherhood shapes views on a variety of issues, but the question remains whether mothers hold distinctive views on gun control policies relative to their non-parent peers. We draw on 2017 Pew Research Center data to explore the ways gender, parenthood, and race intersect to shape attitudes on gun policy in the post-Sandy Hook era when gun violence has become prominently linked with schools and children, and during a time when the Black Lives Matter movement has drawn national attention to the relationship of gun violence and racial inequality. Most notably, we find that contemporary depictions of mothers as a distinctively pro-gun control constituency are largely inaccurate. The very real gender gap in gun policy attitudes appears to be falsely attributed to motherhood, rather than gender. We also find very little impact of parenthood for men. Finally, we generally fail to see much relationship between race, parenthood, and gun attitudes. Overall, despite common belief and media reporting to the contrary, the story is very much one where parenthood seems to play little role in gun policy attitudes.